Khám phá một số yếu tố tác động đến kĩ năng hợp tác của sinh viên theo tiếp cận kĩ năng của thế kỉ XXI - Đặng, Thị Diệu Hiền (Tạp chí Giáo dục, 2025)
In the 21st century, collaboration skill is important and necessary for workers. The development of collaboration skill as well as 21st century approach collaboration skill has always been of interest to educators and trainers at all levels of education. Despite the development efforts, it seems that 21st century approach collaboration skill has not yet reached a good level, so it is still in need of improvement. The results from the exploration of 519 valid responses from first and second-year students at Ho Chi Minh City University of Technology and Education (HCMUTE) revealed that five experiential activities: teamwork, participation in student unions/clubs, scientific research, part-time work, and doing housework, showed significant differences and correlations at the 5% significance level with the 21st collaborative skill. However, only four of them, excluding part-time work, were suitable in the regression model and explained 21.5% of the impact on the 21st collaborative skill. Additionally, the results indicated that students’ 21st collaborative skill was at a fairly good level and did not differ significantly at the 5% level based on some variables such as gender, regular living place before university, type of high school attended, but there were significant differences with average academic results in certain years. Based on these findings, it can be inferred that students’ 21st collaborative skill can be developed not only through academic activities but also through teamwork in any situation, participation in student unions/clubs, scientific research, and doing housework.